2003
DOI: 10.1016/s0140-6736(03)13077-2
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus as a possible cause of severe acute respiratory syndrome

Abstract: A coronavirus was isolated from patients with SARS that might be the primary agent associated with this disease. Serological and molecular tests specific for the virus permitted a definitive laboratory diagnosis to be made and allowed further investigation to define whether other cofactors play a part in disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

42
2,236
7
86

Year Published

2003
2003
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,742 publications
(2,371 citation statements)
references
References 11 publications
42
2,236
7
86
Order By: Relevance
“…After 10 days of illness, more than 90% of samples were positive, confirming the findings of other studies (3,6,9) and showing the diagnostic utility of serology in SARS investigation.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…After 10 days of illness, more than 90% of samples were positive, confirming the findings of other studies (3,6,9) and showing the diagnostic utility of serology in SARS investigation.…”
supporting
confidence: 89%
“…The most reliable laboratory test for the confirmation of SARS is detection of SARS-CoVspecific antibodies (4,8). In Hong Kong, a prospective study of 75 SARS cases demonstrated SARS-CoV IgG seroconversion in 70 (93%) cases by use of an in-house indirect IFA with acetone-fixed SARS-CoV-infected Vero cells, with antibodies detectable at a mean of 20 days (range, 11 to 28) after onset (9). This level of detection was similar to that in the same group's retrospective analysis of 50 cases, where all 32 patients with acute-and convalescent-phase sera demonstrated seroconversion or fourfold rises in SARS-CoV-specific antibody levels by IFA; 280 control sera were negative (8).…”
mentioning
confidence: 99%
“…A novel coronavirus (CoV) has been isolated and identified as the cause of the severe acute respiratory syndrome (SARS), 1 for which there is currently no effective treatment. The SARS CoV genome sequence has been recently published.…”
mentioning
confidence: 99%
“…15,16 Sin embargo, el aislamiento del Coronavirus en múltiples laboratorios alrededor del mundo, utilizando las mismas técnicas moleculares en muestras clínicas respiratorias, apuntaba principalmente a este virus como el posible agente etiológico. 8,[17][18][19] Con el cumplimiento de los postulados de Koch en el modelo animal de primate no humano (Macaca fascicularis) se considera al Coronavirus como el agente causal definitivo del SARS. 20 El 24 de marzo, investigadores del Centro para el Control de las Enfermedades Infecciosas de Atlanta (CDC) y en Hong Kong 3,5,11,15 detectaron, por microscopía electrónica, la presencia del mismo Coronavirus encontrado en Canadá en las secreciones respiratorias de pacientes con el SARS.…”
unclassified
“…A través de estudios de inmunofluorescencia se ha documentado la formación de anticuerpos contra la nueva variedad de Coronavirus en sueros de la fase aguda y de la fase de convalecencia, en pacientes con diagnóstico del SARS. 8,17,19 Peiris y colaboradores demostraron la presencia del Coronavirus en especímenes respiratorios y en suero en 45 de 50 pacientes, provenientes de cinco diferentes brotes del SARS en Hong Kong. Adicionalmente, por cultivos virales se aisló el Coronavirus en dos de estos pacientes.…”
unclassified